COMPUSE CU VALOARE AFECTIVĂ ÎN LIMBA ITALIANĂ LITERARĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
An attempt to highlight the advantages of word composition technique in the Italian literary language is made. Very often writers and poets, while looking for stylistic effects use certain linguistic instruments, one of these being the word formation procedure. We see this approach at different stages in the works of a number of Italian writers distinguished by an original style (Chiabrera, Gadda, Zanzotto, Beni, etc.). One explanation is the need of a stylistic diversity against boring imitations of the standard style. The concise form of the compound word has the power of description and the capacity to highlight certain characteristics, which otherwise would be very difficult, or even impossible, to render. The numerous examples found in the fiction literature demonstrate the unlimited capacity of the language to permanently create new words.